AKUNTABILITAS DAN KORELASINYA DENGAN NILAI UTS MAHASISWA JURUSAN PENDIDIKAN BIOLOGI PADA PENERAPAN METODE KOOPERATIF TIPE GROUP INVESTIGATION DALAM MATA KULIAH BIOLOGI SEL - I Nengah Suka Widana (FPMIPA IKIP PGRI Bali, 2016)
The research objective is to to know how big the performance accountability students in tasks lectures especially in Cell Biology courses based on the indicators that have been established and its correlation with the value of Middle Semester Exam. To achieve these objectives, the research descriptive, correlational. The population used in the form of students majoring in biology education FPMIPA IKIP PGRI Bali, with a purposive sampling techniques, so that all students who programmed the course of Cell Biology automatically selected as sample with the number of 51 students. Data obtained through the performance evaluation process, through observation guided by indicators: peper format; depth study/peper material; performance presentation; ability to answer questions and communication styles. Data midterm exam score is obtained by giving the essay test. Data were analyzed by using descriptive and Pearson Product Moment Correlation analysis using SPSS for windows 20.00. The research findings performance Accountability students in the application of Cooperative Learning Model GI type in the course of Cell Biology, very good category. There is a considerable correlation (r xy = 0.709) between accountability for performance of students with grades midterms achieved in subjects Biology Sel.